I can't even - Jennica, Brigitta Vania (Nanyang Technological University, 2021)
In recent years, the world has been getting increasingly more aware of mental health issues. Besides therapy and consultations, there are more products created to support people with mental health issues, such as mindfulness journals, exercise guides, and even music playlists. However, the products are usually generalized. A self-care kit made specifically for me, <i can’t even> is a way for me to personally retell the story of how I go through difficult days. Through this project, I would like for the audience not only to learn about my experience and about mental health in general, but also to realize that people with mental health issues may have different mindsets and reactions to their situations and encourage the audience to self-reflect on their own mental health.